ĐẶC ĐIỂM DI TRUYỀN PHÂN TỬ CỦA NEISSERIA MENINGITIDIS (SEROGROUPS VÀ GENOSUBTYPES) PHÂN LẬP Ở MỘT SỐ ĐƠN VỊ QUÂN ĐỘI KHU VỰC PHÍA BẮC (2014-2017) - Võ, Viết Cường; Bùi, Thị Lan Anh; Nguyễn, Văn Minh; Triệu, Phi Long (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
MOLECULAR CHARACTERIZATION OF NESERRIA MENGINITIDIS SEROGROUPS AND GENOSUBTYPES ISOLATED IN SOME NORTHERN MILITARY UNITS IN THE PERIOD 2012 - 2015 Based on polysaccharide capsule protein, N. meningitidis was subdivided into 13 serogroups. The distribution of serogroups depended on time and geographic areas. Most of these invasive disease cases are strains belonging to serogroups A, B, C, Y, and W-135. PorA is an outer membrane protein of most meningococcal isolates which contains two major variable regions (VR1 and VR2). Determination of VR1 and VR2 regions in porA gene plays very important role in epidemiology examination and vaccine production. Studying the structure of serogroups and genosubtypes of N. meningitidis isolated in several northern military units in period 2014 - 2017 showed that the serogroup B contributed to the highest rate which was estimated in 79.17%, followed serogroup C (6.25%), and the remaining rates belongs to the other serogroups except serogroups A, B, C, W135, and Y. The results for determination of genosubtype based on VR1 and VR2 regions of porA gene in 38 strains indicated that the highest genosubtypes were P1.22-25,14 (34,2%), followed P1.7-2,13-1 (10,5%). Other genosubtypes accounted from 2,6% to 7,9%. 7 strains (18,4%) were non-genosubtypeable.